Cross on the star of David : the Christian world in Israel's foreign policy, 1948-1967 - Bialer, Uri (Indiana series in Middle East studies., 2005)
Cross on the Star of David presents the first scholarly analysis, based on newly declassified documents, of Israeli policymaking on the stance of the Christian world toward the new state of Israel. Bailer focuses on the impact that modes of thinking rooted in the historical tradition of Jewish-Christian interactions had on Israeli policymakers and concludes that they were not innocent of the perceptions and biases that influenced the Christian world's behavior toward Israel.